Change in Leukocyte Telomere Length Predicts Mortality in Patients with Stable Coronary Heart Disease from the Heart and Soul Study - Goglin, Sarah E. (PLoS One, 2016)
BACKGROUND: Short telomere length independently predicts mortality in patients with coronary heart disease. Whether 5-year change in telomere length predicts subsequent mortality in patients with coronary heart disease has not been evaluated. METHODS: In a prospective cohort study of 608 individuals with stable coronary artery disease, we measured leukocyte telomere length at baseline and after five years of follow-up. We divided the sample into tertiles of telomere change: shortened, maintained or lengthened. We used Cox survival models to evaluate 5-year change in telomere length as a predictor of mortality. RESULTS: During an average of 4.2 years follow-up, there were 149 deaths. Change in telomere length was inversely predictive of all-cause mortality. Using the continuous variable of telomere length change, each standard deviation (325 base pair) greater increase in telomere length was associated with a 24% reduction in mortality (HR 0.76, 95% CI 0.61–0.94; p = 0.01), adjusted for age, sex, waist to hip ratio, exercise capacity, LV ejection fraction, serum creatinine, and year 5 telomere length. Mortality occurred in 39% (79/203) of patients who experienced telomere shortening, 22% (45/203) of patients whose telomere length was maintained, and 12% (25/202) of patients who experienced telomere lengthening (p<0.001). As compared with patients whose telomere length was maintained, those who experienced telomere lengthening were 56% less likely to die (HR 0.44, 95% CI, 0.23–0.87). CONCLUSIONS: In patients with coronary heart disease, an increase in leukocyte telomere length over 5 years is associated with decreased mortality.